Youth Response to State Cyberbullying Laws - Kabir Dasgupta (Auckland University of Technology (AUT), Faculty of Business, Economics and Law, 2016)
Cyberbullying is a large social concern among youth in the US. This is the first empirical study to examine how high-school teenagers respond to cyberbullying laws that require schools to enact effective guidelines to reduce cyberbullying. The analysis utilizes nationally representative samples of high-school students from Youth Risk Behavior Surveys and incorporates state and time variation in the implementation of cyberbullying laws to estimate the causal impacts of the law in a difference-in-differences framework. Key results indicate that adoption of cyberbullying law is related to statistically significant increases in the likelihood that students report experiences of being victimized by various forms of school violence. Further empirical tests reveal (to some degree) that the state laws are potentiallymore likely to promote victims' reporting of school violence/ cyberbullying victimization experiences. Finally, evaluation of important components of the state laws indicate that compared to other legislative provisions, criminal sanctions are more likely to increase victims' reporting of school violence victimization. The regression estimates are robust to the inclusion of multiple sensitivity checks.
Keywords: I28; I12; K32; 330; Cyberbullying Laws; Electronic Harassment; Youth; Youth Reporting; School Violence; Mental Health; Difference-in-differences